2014
DOI: 10.1016/j.jacc.2014.04.029
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Randomized Evaluation of the Watchman Left Atrial Appendage Closure Device in Patients With Atrial Fibrillation Versus Long-Term Warfarin Therapy

Abstract: In this trial, LAA occlusion was noninferior to warfarin for ischemic stroke prevention or SE >7 days' post-procedure. Although noninferiority was not achieved for overall efficacy, event rates were low and numerically comparable in both arms. Procedural safety has significantly improved. This trial provides additional data that LAA occlusion is a reasonable alternative to warfarin therapy for stroke prevention in patients with NVAF who do not have an absolute contraindication to short-term warfarin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
1,149
12
38

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,533 publications
(1,240 citation statements)
references
References 29 publications
41
1,149
12
38
Order By: Relevance
“…Nie można w związku z tym zalecać leczenia przeciwpłytkowego w celu prewencji udaru mózgu u pacjentów z AF. [449][450][451]. Te dane wskazują, że zamykanie LAA było nie gorsze niż leczenie za pomocą VKA pod względem zapobiegania udarom mózgu u pacjentów z AF z grupy umiarkowanego ryzyka udaru, z możliwością mniejszej częstości występowania krwawień u pacjentów, u których uzyskano dane z dłuższej obserwacji [452,453].…”
Section: Leczenie Przeciwpłytkowe Jako Postępowanie Alternatywne W Stunclassified
“…Nie można w związku z tym zalecać leczenia przeciwpłytkowego w celu prewencji udaru mózgu u pacjentów z AF. [449][450][451]. Te dane wskazują, że zamykanie LAA było nie gorsze niż leczenie za pomocą VKA pod względem zapobiegania udarom mózgu u pacjentów z AF z grupy umiarkowanego ryzyka udaru, z możliwością mniejszej częstości występowania krwawień u pacjentów, u których uzyskano dane z dłuższej obserwacji [452,453].…”
Section: Leczenie Przeciwpłytkowe Jako Postępowanie Alternatywne W Stunclassified
“…Although this noninferiority margin is wide, it is similar to margins used in other major clinical trials in cardiology. [26][27][28][29][30][31][32] The event rates were lower than had been expected, because the number of patients with an acute coronary syndrome who were enrolled in the trial was lower than had been anticipated. However, when we used the prespecified noninferiority margin to test the actual event rate among the prespecified number of patients, we found that iFR was noninferior to FFR even when the upper limit of a one-sided 99.5% confidence interval was used.…”
mentioning
confidence: 88%
“…Device embolization may be diagnosed by fluoroscopy, chest X-ray, TTE, TOE or CCTA (Fig 7, panel C). Pericardial effusion incidence is decreasing with last generation of devices, standardization and better understanding of the procedure [2]. Pericardial effusion occurs mostly…”
Section: Complicationsmentioning
confidence: 99%
“…Two randomized-controlled trials, the PROTECT AF and PRE-VAIL studies, have shown the safety and efficacy of this procedure in patients randomized to either LAA closure with the WATCHMAN device (Boston Scientific, Natick, MA, USA) or warfarin therapy [1,2]. Two large registries in patients who were mostly contra-indicated or deemed unsuitable to long-term anticoagulation and treated with the Amplatzer Cardiac Plug (ACP) (St. Jude Medical/Abbott, St Paul, MN, USA) (ACP multicenter registry) [3] or the WATCHMAN (Ewolution registry) [4] have confirmed safety and efficacy of this procedure in this population.…”
Section: Introductionmentioning
confidence: 99%